INOVASI PEMBELAJARAN MELALUI KOMBINASI MODEL KOOPERATIF STAD DENGAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI SEL DI KELAS XI MIA 5 SMA NEGERI 5 MEDAN - Saudur E Sianipar; Aprianika H Tarigan; Tuti W Bako (Jurnal Pelita Pendidikan, 2016)
The study was implemented to improve learning outcomes and students activity in subject matter ofcell with innovation learning throught combination of cooperative model of STAD (Student TeamsAchievement Division) with Snowball throwing in Class XI MIA 5 SMA Negeri 5 Medan. This study is aclassroom action research (CAR) is performed in two cycle research. This research was conducted by directobservation of teacher (researcher) and students. The observer implementation of research conducted by fourresearch associates and biologys teacher in class XI MIA 5 SMA Negeri 5 Medan. Observations carried out on35 students. Indicator of success research include: classical learning exhaustiveness and student activityobservation. The result of this study indicate that the average value of the pretest students before the learningprocess carried out by using a combination cooperative model of STAD (Student Teams Achivement Division)with Snowball Throwing is 49,7 while the average in Postest I is 68,7. Exhaustiveness percentage of studentsstudying in the cycle I amounting to 60%, this has yet to achieve exhaustiveness criterion in the clasiccal stylebecause it has not reached ≥85%. In cyle II obtained the average value of student learning outcomes by 82,1and there are 31 students who completed the criteria included in the study. Percentage of students in learningexhaustiveness second cyle is 88,5. Increase of classical learning completeness of cycle I to cycle II is 18%.Based on the average percentage of student who are active in cyle I and cycle II is obtained by increasingstudent activity in the cyle I mean the percentage level of activity of student is 62,85% and the second cyleincreased to 85,71%. Increase student activity from cycle I to cyle II was 22,86%. As well as increased activity ofteacher from 66,25% in cycle I increased to 86,25 in cycle II. Increase of teachers activity by 20%. From theabove explanation, it can be concluded that this research can improve of learning outcomes and studentactivity.Keywords: Learning Outcomes, Student Activity, STAD (Student Teams Achievement Division), SnowballThrowing, Classroom Action Research.